Methods used to examine technology in relation to the quality of nursing work in acute care: A systematic integrative review. Issue 9 (28th February 2020) - Redley, Bernice; Douglas, Tracy; Botti, Mari
Abstract: Aims and objectives: To systematically locate, assess and synthesise research to describe methods used to examine technology in relation to the quality of nursing work in acute care. Specific objectives were to (a) describe the types of nursing work examined; (b) describe methods used to examine technology in nursing work; (c) identify outcomes used to evaluate technology in relation to the quality of nursing work; and (d) make recommendations for future research. Background: New technologies can offer numerous benefits to nurses; however, it is challenging to evaluate health information technologies in relation to the quality of nurses' complex day‐to‐day work. Design: A systematic integrative review using a five‐step process. Methods: Five databases were searched using search terms "nurs*, " "workload, " "task, " "time." Data screening, extraction and interpretation were conducted independently by at least two authors and agreement verified by discussion. Data extraction followed PRISMA guidelines. Results: Of the 41 studies included, most (87.8%, n = 36) examined physical dimensions of nursing work; 31.7% ( n = 13) organisational dimensions; 17.1% ( n = 8) cognitive dimensions; and only 12.2% ( n = 5) emotional dimensions. More than half (58.5%, n = 24) examined only one dimension; one captured all four dimensions. Most frequently examined technologies were electronic medical/health records (36.5%) and electronic medication management (19.5%). Direct observation (58.8%, n = 28) and multiple methods (19.5%, n = 8) were the most common methods; nurse tasks, frequency, duration and time distribution were variables most often measured. Conclusions: Examinations of technology in nursing work often failed to capture the multiple dimensions of this work nor did they recognise the complexity of day‐to‐day nursing work in acute care. There is a paucity of literature to inform how and what technology should be measured in relation to the quality of nursing care. Relevance to clinical practice: The outcomes inform useful research methods to comprehensively examine technology to enhance the quality of complex nursing work.